Nghiên cứu ảnh hưởng của các chất xúc tiến (M = Mn, Ce, Zr, và Cr) đối với hoạt tính xúc tác của vật liệu 15%Co/0,05m-SBA-15 trong phản ứng tổng hợp Fischer-Tropsch - Đồng, Đỗ Xuân; Quang, Dương Tuấn; Vinh, Trần Quang; Vũ, Nguyễn Anh; Hiếu, Bùi Quang; Hưng, Nguyễn Việt; Hà, Hoàng Trọng; Hoài Nam, Lê Thị (Vietnam Journal of Chemistry, 2016)
This paper presents the effect of metal promoters (M = Ce, Cr, Mn  and Zr) on the catalytic performance of 15%Co/0.05M-SBA-15 catalysts for the Fischer- Tropsch synthesis. The results showed that the promoters were on SBA-15 influenced on the contribution of Co particles (shape, size, dispersion) on the walls of M-SBA-15 materials. These changes not only increased CO conversion but also significantly increased the liquid product C5+ selectivity. Catalysts were characterized by BET, XRD, TEM, UV-vis, H2-TPR, TPD-NH3, ICP. The catalytic performances of catalysts for Fischer-Tropsch synthesis were tested in a fixed bed reactor. The liquid product was analyzed by GC-MS to calculate hydrocarbon selectivity.